The Effectiveness of Patient Safety In Reducing Patient Safety Incidents - Eppy Setyowati; Febi Ariska Putri; Wiwin Handayani; Kristianingrum Kristianingrum (GLOBAL HEALTH SCIENCE GROUP, 2026)
Patient safety incidents (PSIs) continue to pose serious challenges to healthcare quality and public trust. The persistence of adverse events, near misses, and medical errors indicates that patient safety implementation remains inadequate, often due to weak reporting cultures, limited healthcare worker competence, and insufficient risk management systems. This study aimed to synthesize evidence on the effect of patient safety implementation in reducing patient safety incidents in healthcare services. A literature review was conducted on studies published between 2020 and 2025 using PubMed, Google Scholar, Semantic Scholar, and ScienceDirect. From 1,833 identified articles, duplicates were removed, titles and abstracts were screened, and methodological quality was assessed using the JBI Critical Appraisal Checklist. Seven eligible articles were included and analyzed through narrative synthesis. The findings show that effective patient safety implementation reduces patient safety incidents through four main components: incident reporting systems, strengthening safety culture, improving healthcare worker competence through education, and utilizing information technology for reporting and rapid response. These strategies enhance risk identification, procedural compliance, and prevention of recurrent incidents. Patient safety implementation significantly reduces patient safety incidents and improves healthcare service quality. Comprehensive strategies, managerial support, and continuous non-punitive reporting systems are essential for sustainable patient safety improvement.